Passivation of the TiO2 Surface and Promotion of N719 Dye Anchoring with Poly(4-vinylpyridine) for Efficient and Stable Dye-Sensitized Solar Cells - Daniela Rodrigues (2021)
Dye-sensitized solar cells (DSSCs) have turned to be the most promising PV technology for indoor applications, for sustainable powering billions of IoT devices and wireless indoor sensors; DSSCs are aesthetic, cheap, and safe, and they display extremely high power conversion efficiencies (PCEs). In this study, poly(4-vinylpyridine) (P4VP) of molecular weights (MW) ranging from 2.8 to 18.5k was prepared by reversible addition-fragmentation chain transfer (RAFT) polymerization and studied as a new co-adsorbent with N719 dye to produce efficient DSSCs. P4VP adsorbs on TiO2 via coordinative bonding to the Lewis acid centers of the titania. The adsorbed P4VP effectively hampers the back-electron recombination at the photoanode/electrolyte interface and promotes stronger covalent dye bonding. The simultaneous adsorption of P4VP with N719 allowed reaching a PCE of ca. 7.5% under 1 Sun and with almost half dye loading of the reference device. Sequential adsorption of the P4VP led to a noticeable increase of the strongly covalent bonded dye fraction making the electron injection to the titania more efficient and improving the photocurrent density. The effect of polymer MW, concentration, and adsorption sequence with the N719 on the photovoltaic performance of the DSSCs is discussed. For the first time ever, the efficient long-chain polymeric P4VP co-adsorbent rendered a device with as high PCE as 9% under 1 Sun illumination and 22.5% under indoor 1000 lx light. The PCE history under natural aging suggests that P4VP is a high-performing co-adsorbent, which allows fabrication of quite stable devices.